2009
DOI: 10.1080/10494820701706437
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative versus individual use of regulative software scaffolds during scientific inquiry learning

Abstract: Scaffolds to plan, monitor, and evaluate learning within technology-enhanced inquiry and modeling environments are often little used by students. One reason may be that students frequently work collaboratively in these settings and their group work may interfere with the use of regulative supports. This research compared the use of regulative scaffolds within an inquiry and modeling environment by paired and single students. Pairs were predicted to make less use of regulative scaffolds than singles. To validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 40 publications
(49 reference statements)
3
16
0
Order By: Relevance
“…One possible reason for this result is that the students discussed scientific knowledge with their peers and interacted simultaneously to solve problems, clarify scientific concepts, and improve their learning performance in the science course. Thus, the CL approach combined with other inquiry-based learning models can help students achieve significantly higher learning outcomes compared with individual students (Bell et al, 2010;Hong et al, 2014;Manlove et al, 2009;Vogel et al, 2010). The results presented here support previous studies.…”
Section: Students Achieved Significantly Better Learning Performancessupporting
confidence: 82%
See 1 more Smart Citation
“…One possible reason for this result is that the students discussed scientific knowledge with their peers and interacted simultaneously to solve problems, clarify scientific concepts, and improve their learning performance in the science course. Thus, the CL approach combined with other inquiry-based learning models can help students achieve significantly higher learning outcomes compared with individual students (Bell et al, 2010;Hong et al, 2014;Manlove et al, 2009;Vogel et al, 2010). The results presented here support previous studies.…”
Section: Students Achieved Significantly Better Learning Performancessupporting
confidence: 82%
“…Vogel, Spikol, Kurti, and Milrad (2010) used CL to help teachers infuse inquiry into a standards-based science curriculum. Manlove, Lazonder, and de Jong (2009) compared the use of regulative scaffolds within an inquiry and modeling environment between paired and single students. The results from these studies showed that CL can improve students' scientific learning motivation and learning performance.…”
Section: Releated Literaturementioning
confidence: 99%
“…Another understanding mentions science process skills are all necessary skills to acquire, develop, and apply the concepts, laws, and theories of science, both in the form of mental skills, physical skills as well as social skills [3]. This definition gives the sense that the process of skills not only in the form of physical skills in the form of the action, but can also be mental and social skills that can be applied in scientific activities [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although offering regulatory guidelines during collaborative scientific discovery learning leads to improved planning activities, the results for monitoring activities are less conclusive. In a more recent study by Manlove, Lazonder, and de Jong (2009) that also focused on regulatory software scaffolds during scientific inquiry learning, the researchers were especially interested in whether there is a difference between paired and single students as far as the use of regulative scaffolds is concerned. The results show that the pairs scored significantly better than individual students on learning outcomes (dreport structure = 0.23, dreport content = 0.83 and dmodel quality = 1.16, a very large effect).…”
Section: Supporting Scientific Discovery Learningmentioning
confidence: 99%